Assistance in the implementation of the waste bank information system at the waste bank “Wiguna”, Sugihmas - Agus Setiawan; Endah Ratna Arumi; Disyana Ajeng Pramesti (Community Empowerment, 2021)
The waste generated by industry and households promotes intensive waste management. However, because the government fails to manage the waste, the community must play an active role in assisting. Plastic waste is a dangerous waste if not managed properly, so that the Wiguna Waste Bank is present with anxiety about the dangers of waste. The administrative management of the Wiguna waste bank still uses conventional bookkeeping. As a result, an information system was created to aid in the administration of the waste bank. The system was designed with the primary features of personal data, waste data, deposit notes, and savings. Waste bank managers benefit from the information system because reports can be easily generated, allowing the principle of accountability to be met.